Coloring of master brake cover accessories (CNC products) using the anodizing method with natural mangosteen peel dye - Arif Budi Wicaksono; Nurgesang Faisal Arif; Ardianto Vicky Teno (Prosiding SNTTM, 2025)
This research focuses on the coloring of brake master cover (CNC products) using anodizing method with natural dye from mangosteen peel (Garcinia mangostana L.). The utilization of natural dyes aims to replace synthetic dyes that have the potential to negatively impact the environment. In this study, aluminum samples were used as substrates, which were then subjected to anodizing process with variations in voltage and electrolysis time. Mangosteen peel extract was obtained through a simple extraction method and used as a coloring solution. Tests carried out include color characterization, corrosion resistance, and adhesion of the dye layer on the aluminum surface. The results showed that mangosteen peel natural dye can provide an even color on the surface of anodized aluminum, with varying color intensity depending on the process parameters. In addition, the resulting coating has good corrosion resistance and strong adhesion. Thus, this method has potential as an environmentally friendly alternative in the coloring of aluminum-based products.